An Assessment of the Influence of Calabar Carnival on the Economy of the Residents of Calabar Metropolis, Cross River State, Nigeria (Global Journal of Human-Social Science, 2012)
This study investigated the influence of Calabar Carnival on the economy of the residents of Calabar Metropolis of Cross River State, Nigeria. Special focus was on the resident's income from tourism jobs and related activities during the period of the Christmas festival celebration in the state. Information for the study was basically from the questionnaire survey and participatory research method. The generated data were analyzed using descriptive statistics such as mean, simple percentages and graphic illustrations. The study demonstrated that there was a steady increase in the number of tourists' visits for the Christmas festival with a corresponding increase in the number of people involved in tourism related activities during the time under investigation, with the greatest number of people involved in trading during this time and recording the highest income. The result shows that tourism influenced economic activities vis-à-vis enhancement of the people's income in the area. Based on the above findings, it is recommended that all stakeholders in the tourism industry should be involved in the planning and execution of tourism projects and that tourism activities be organized all through the year to ensure more tourists visitation and avoid seasonality in the tourism industry.
Keywords: Tourism; Influence; Carnival; Economic development; Residents